2012
DOI: 10.3133/sir20125002
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of long-term water-level declines in basalt aquifers near Mosier, Oregon

Abstract: Center Looking southwest across Mosier Valley toward Mt. Hood, Oregon. Newly planted cherry trees (foreground) transition into mature cherry trees (red foliage) with grape vineyards in the backgroud (yellow foliage). (Photograph taken by Jonathan Haynes, U.S. Geological Survey, 2007). Right Looking southwest along the Columbia RIver toward the Mosier syncline and the the City of Mosier, Oregon.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(20 citation statements)
references
References 8 publications
0
20
0
Order By: Relevance
“…Previous research has shown significant declines of up to 40 to 60 m in groundwater levels since the 1960s and 1970s in the Mosier area (Lite and Grondin, 1988;Burns et al, 2012;Lite, 2013). Groundwater is utilized extensively for the commercial irrigation of cherry orchards and as drinking water for the entire watershed.…”
Section: Previous Workmentioning
confidence: 99%
See 4 more Smart Citations
“…Previous research has shown significant declines of up to 40 to 60 m in groundwater levels since the 1960s and 1970s in the Mosier area (Lite and Grondin, 1988;Burns et al, 2012;Lite, 2013). Groundwater is utilized extensively for the commercial irrigation of cherry orchards and as drinking water for the entire watershed.…”
Section: Previous Workmentioning
confidence: 99%
“…Although not labeled, the Rocky Prairie anticline is just north of the thrust fault. The shaded portion is the OWRD Administrative area and the circles are the Mosier area wells (Burns et al, 2012, compiled from Newcomb (1969, Swanson et al (1981), Lite and Grondin (1988), Kienle (1995), and Jervey (1996) Lite and Grondin, 1988;Reidel et al, 2002;Tolan et al, 2009;and Lite, 2013). Newcomb (1969), Lite and Grondin (1988), McClaughry et al (2012), and Lite (2013 Newcomb (1969), Lite and Grondin (1988), and Burns et al (2012).…”
Section: Geochemical Signatures 67mentioning
confidence: 99%
See 3 more Smart Citations